Thermosensory Signaling by TRPM Is Processed by Brain Serotonergic Neurons to Produce Planarian Thermotaxis - Inoue, Takeshi (J Neurosci, 2014)
For most organisms, sensitive recognition of even slight changes in environmental temperature is essential for adjusting their behavioral strategies to ensure homeostasis and survival. However, much remains to be understood about the molecular and cellular processes that regulate thermosensation and the corresponding behavioral responses. Planarians display clear thermotaxis, although they have a relatively simple brain. Here, we devised a quantitative thermotaxis assay and unraveled a neural pathway involved in planarian thermotaxis by combinatory behavioral assays and RNAi analysis. We found that thermosensory neurons that expressed a planarian Dugesia japonica homolog of the Transient Receptor Potential Melastatin family a (DjTRPMa) gene were required for the thermotaxis. Interestingly, although these thermosensory neurons are distributed throughout their body, planarians with a dysfunctional brain due to regeneration-dependent conditional gene knockdown (Readyknock) of the synaptotagmin gene completely lost their thermotactic behavior. These results suggest that brain function is required as a central processor for the thermosensory response. Therefore, we investigated the type(s) of brain neurons involved in processing the thermal signals by gene knockdown of limiting enzymes for neurotransmitter biosynthesis in the brain. We found that serotonergic neurons with dendrites that were elongated toward DjTRPMa-expressing thermosensory neurons might be required for the processing of signals from thermosensory neurons that results in thermotaxis. These results suggest that serotonergic neurons in the brain may interact with thermosensory neurons activated by TRPM ion channels to produce thermotaxis in planarians.